PENGARUH MODEL SPORT EDUCATION TERHADAP MOTIVASI BELAJAR SISWA SD NEGERI 107440 PEMATANG SETRAK - Irawan, Jodi; Siregar, Samsuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the sport education Model on the learning motivation of students SD Negeri 107440 Pematang Serak. This type of research is quantitative reaserch and the reaserch method used is experimental research. The population in this study were all grades IV and V of SD Negeri 107440 Pematang Serak. The data collection technique used was a questionnaire. The time of the study was conducted in the even semester of the 2024-2025 academic year for 3 weeks. The research sample was carried out in grade IV as an experimental class of 33 students using the Sport Education Model and grade V as a control class of 37 students using the conventional model. The instrument in the study used a questionnaire. This data analysis technique uses the t-test (Independent Sample T-test) to test the hypothesis. The schedule of the hypothesis result obtained is 0.000 < 0.05 so it can be concluded that Ha is accepted and H0 is rejected. Which means that there is a significant influence of the use of the Sport Education Model on the Learning Motivation of Students of SD Negeri 107440 Pematang Serak.